Glomerular filtration in the aging population - Noronha, Irene L.; Santa-Catharina, Guilherme P.; Andrade, Lucia; Coelho, Venceslau A.; Jacob-Filho, Wilson; Elias, Rosilene M. (Frontiers in Medicine, 2022)
In the last decades, improvements in the average life expectancy in the world population have been associated with a significant increase in the proportion of elderly people, in parallel with a higher prevalence of non-communicable diseases, such as hypertension and diabetes. As the kidney is a common target organ of a variety of diseases, an adequate evaluation of renal function in the approach of this population is of special relevance. It is also known that the kidneys undergo aging-related changes expressed by a decline in the glomerular filtration rate (GFR), reflecting the loss of kidney function, either by a natural senescence process associated with healthy aging or by the length of exposure to diseases with potential kidney damage. Accurate assessment of renal function in the older population is of particular importance to evaluate the degree of kidney function loss, enabling tailored therapeutic interventions. The present review addresses relevant topics in the understanding of the influence of age on glomerular filtration, highlighting the structural and functional changes associated with normal healthy aging leading to age related loss of kidney function. A review of the different options for evaluating GFR in the elderly population through GFR measurement or by using prediction equations for estimating GFR is also presented. This review may support clinicians for the interpretation and management of changes in GFR in the older population.